Teaching and Learning Process of Decision-Making Units in Talented Young Players From U-10 to U-14 - Pastor-Vicedo, Juan Carlos; Prieto-Ayuso, Alejandro; Contreras-Jordán, Onofre Ricardo; Clemente, Filipe Manuel; Nikolaidis, Pantelis Theo; Rosemann, Thomas Johannes; Knechtle, Beat (Frontiers in Psychology, 2020)
There are multiple factors that have been studied for talent identification (TI) with regard to sport performance, such as physical and physiological parameters, psychological, social and contextual, and technical-tactical. However, despite the importance of these indicators for reaching the elite, new trends seem to assure that one of the key elements in a young player is Decision-Making (DM). Thus, in the last decades, research DM in young players has increased. Nevertheless, very few has been done in relation with DM and talented players. The purpose of this study was to analyse and compare the effectiveness, number and duration of Decision-Making Units (DMUs) of three groups of talented young players in U-10, U-12 and U-14 levels. Ninety-seven youth players participated in the study. A total of 1087 actions were analyzed. The Nomination Scale for Identifying Football Talent was utilised to screen the talent pool (N = 18) and the Game Performance Evaluation Tool was used for analysing the 1087 actions completed. The results showed that the effectiveness in children has to more than 80% to be considered as talented. Moreover, a greater effectiveness of DMUs was shown as older age group. The game speed also increased with age. It was revealed that U-12 did not follow the progression in the decisional demands in the formative stages. It is highlighted, therefore, the necessity of reviewing the organizational aspects in the U-12 age group, related mainly to the size of the pitch and the number of players, due to it does not follow the same progression in regard to decisional demands. Future studies should follow this study with U-16, U-18 and U-23 age groups, with the purpose of knowing the effectiveness, duration and number of DMUs in older age groups. Furthermore, policy makers and teachers/coaches from both educational and soccer context must take these results into account, with the purpose of adjusting the teaching and learning process of talented children in sport.